2021
DOI: 10.1038/s41385-021-00401-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of miR-99a-5p prevents allergen-driven airway exacerbations without compromising type-2 memory responses in the intestine following helminth infection

Abstract: Acute exacerbations (AE) of asthma, remain one of the biggest concerns for patients living with asthma. As such, identifying the causes, the molecular mechanisms involved and new therapeutic interventions to prevent AE is a high priority. Immunity to intestinal helminths involves the reactivation of type-2 immune responses leading to smooth muscle contraction and mucus hypersecretion–physiological processes very similar to acute exacerbations in the airways following allergen exposure. In this study, we employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…8-Hydroxycirsimaritin and methyl rosmarinate interacted with 21 miRNAs, regulating inflammation and apoptosis by targeting PIK3CB, MAPK1, STAT3, EGFR, and AKT (according to the topological parameters). In total, 15 compounds, including caffeic acid, luteolin, esculetin, chrysin, and methyl rosmarinate, cooperatively interacted with miR-99a, contributing to NF- κ B-induced inflammatory cytokine production, T-cell activation, and allergen-driven exacerbations of airway disease [ 59 61 ]. Notably, maslinic acid and 20 β -hydroxyursolic acid interact with the same binding miRNAs (miR-33b, miR-18a, miR-99a, and miR-328) and mRNA targets (ESR1 and PTPN6).…”
Section: Discussionmentioning
confidence: 99%
“…8-Hydroxycirsimaritin and methyl rosmarinate interacted with 21 miRNAs, regulating inflammation and apoptosis by targeting PIK3CB, MAPK1, STAT3, EGFR, and AKT (according to the topological parameters). In total, 15 compounds, including caffeic acid, luteolin, esculetin, chrysin, and methyl rosmarinate, cooperatively interacted with miR-99a, contributing to NF- κ B-induced inflammatory cytokine production, T-cell activation, and allergen-driven exacerbations of airway disease [ 59 61 ]. Notably, maslinic acid and 20 β -hydroxyursolic acid interact with the same binding miRNAs (miR-33b, miR-18a, miR-99a, and miR-328) and mRNA targets (ESR1 and PTPN6).…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs constitute a class of small single-stranded noncoding RNA, and thousands of miRNAs are believed to be involved in metabolism, signal transduction, cell adhesion, cell motility, cell differentiation, and apoptosis [ 20 22 ]. Therefore, for different earmark genes and cancer types, miRNAs have been observed to be both oncogenes and tumor suppressors [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, increasing attention to the cause of the above trend should be paid. Several previous studies have revealed that the expression level of miR-99a-5p might be related to inflammation and immune responses [38][39][40]. Since AS was a chronic inflammatory disease [41,42], we then explored whether miR-99a-5p could affect inflammatory cytokines.…”
mentioning
confidence: 99%